NU7441 Enhances the Radiosensitivity of Liver Cancer Cells - Chuanjie Yang; Quanxu Wang; Xiaodan Liu; Xiulian Cheng; Xiaoyu Jiang; Yuan Zhang; Zhijie Feng; Pingkun Zhou (Cellular Physiology and Biochemistry, 2016)
Objective: Radiation therapy, one of the major treatments for liver cancer, causes DNA damage and cell death. Since the liver cancer cells have a strong capacity to repair irradiative injury, new medicines to enhance this treatment are urgently required. In this study, we investigated the effect of NU7441, a synthetic small-molecule compound, as a specific inhibitor of DNA-dependent protein kinase (DNA-PK) in radiosensitization of hepatocellular carcinoma HepG2 cells. Methods: Cell Counting Kit-8 (CCK-8) was first used to evaluate the proliferation of HepG2 cells under NU7441 treatment. SDS-PAGE and Western blot were then performed to study the protein expression leading to the DNA damage repair. Further, neutral single cell gel electrophoresis and immunofluorescence assay were carried out to assess DNA repair. Finally, flow cytometry was implemented to examine the changes in cell cycle. Results: NU7441 reduced the CCK-8 counts in the HepG2 culture, further enhanced 60Coγ radiation injury to HepG2 cells, which was manifested by decreasing the DNA-PKcs (S2056) protein expression, increasing γH2AX foci number, prolonging the tail moment of the comet cells, and inducing cell cycle arrest at G2/M phase. Conclusion: NU7441 inhibited the growth of liver cancer cells, enhanced the radiosensitization of these cancer cells by interfering with the DNA repair and cell cycle checkpoint. These data implicate NU7441 as a potential radiotherapy sensitizer for the treatment of liver cancer.